The living planet - Attenborough, David, 1926- (Sydney : BBC Enterprises Ltd., 1984)
Sir David Attenborough examines the earth's environments one by one to see how the survivors of ancient groups, and the representatives of newly evolved ones, have colonized and adapted to their visible surroundings - and each other.
v.1. The building of the earth - v.2. The frozen world - v.3. The Northern forest - v.4. Jungle - v.5. Seas of grass- v.6. The baking deserts v.7. The sky above v.8. Sweet fresh water v.9. The margins of the land v.10. Worlds apart v.11. The open ocean - v.12. New world
Backup avaiable in VHS 1/2 in.
Copy available in DVD format.
Keywords: Ecology; Life (Biology).